AN ANALYSIS OF TENSES USED IN FINDING NEMO MOVIE SCRIPT: THE RELEVANCE TO 2013 CURRICULUM FOR TEACHING TENSES TO JUNIOR HIGH SCHOOL STUDENTS - Khozin HS, Nada Rona Amiroh; Muflihah, Tatik (Universitas Islam Balitar, 2020)
This research aims to find out types of tenses used in Finding Nemo movie script and the relevance to 2013 curriculum for teaching tenses to junior high school students. The 2013 curriculum is used as the standard guideline to determine the sentences’ appropriateness. This study was a descriptive qualitative method by employing content analysis technique to analyze the data. The data resources were documented from the script movie and 2013 English curriculum. The findings are presented in the form ofthe sentences that were analyzed and classified into six types of tenses. These six tenses matched for the curriculum, they were Simple Present Tense, Simple Past Tense, Present Continuous Tense, Past Continuous Tense, Present Perfect Tense, and Present Future Tense.The result indicated there was a high frequency of the tenses in the sentences with total number 96%.This study concluded that Finding Nemomovie script can be used as supporting material by English teachers to teach tenses for junior high school students, particularly Simple Present Tense which is the most used tense in the movie.